2010
DOI: 10.1001/jama.2010.1705
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinoscopy vs Endosonography for Mediastinal Nodal Staging of Lung Cancer

Abstract: UNG CANCER IS THE MOST COMmonly diagnosed cancer worldwide (1.35 million/year) and also the most frequent cause of cancer death (1.18 million/year). 1 Clinical staging of lung cancer is an integral part of patient care because it directs therapy and has prognostic value. Imaging with computed tomography (CT) is valuable for assessing the primary tumor (T-stage) while fluorodeoxyglucose positron emission tomography (PET) is valuable for detecting metastases. In cases where the primary tumor is resectable and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
374
2
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(407 citation statements)
references
References 28 publications
9
374
2
11
Order By: Relevance
“…Therefore, while diagnostic accuracy of EBUS-TBNA for detection of NSCLC matches [30], or even exceeds [31], that of mediastinoscopy, the accuracy in determination of NSCLC subtype remains unclear. One study examined accuracy of EBUS-TBNA in subtype determination in 23 specimens (retrospectively selected from over 1,800 EBUS-TBNA procedures performed) [32].…”
Section: Lung Cancer Dp Steinfort Et Almentioning
confidence: 99%
“…Therefore, while diagnostic accuracy of EBUS-TBNA for detection of NSCLC matches [30], or even exceeds [31], that of mediastinoscopy, the accuracy in determination of NSCLC subtype remains unclear. One study examined accuracy of EBUS-TBNA in subtype determination in 23 specimens (retrospectively selected from over 1,800 EBUS-TBNA procedures performed) [32].…”
Section: Lung Cancer Dp Steinfort Et Almentioning
confidence: 99%
“…The sensitivity of EBUS increased to 94% in a subgroup of patients selected with imaging compared with only 76% in patients who had no PET or CT selection. The ASTER [Assessment of Surgical sTaging versus EBUS and endoscopic ultrasound (EUS) in lung cancer: a Randomized controlled trial] study randomized 241 patients with resectable lung cancer with enlarged or FDG-avid hilar or mediastinal lymph nodes or a central lung lesion to immediate surgical staging or minimally invasive staging with EBUS and EUS followed by surgical staging if no mediastinal nodal metastases were found (21). The combination strategy resulted in sensitivity of 94% (95% CI, 85%-98%) compared with only 79% (95% CI, 66%-88%) with surgical staging alone (P ¼ 0.02).…”
Section: Stagingmentioning
confidence: 99%
“…Cerfolio et al found in these patients that EBUS-TBNA and EBUS-FNA had a NPV of 79% and sensitivity of only 57%; EBUS alone had a NPV of 80% and sensitivity of 63% but mediastinoscopy faired significantly better with 88% sensitivity, 93% NPV and 95% accuracy. 6 Despite these findings many have used the alternative results of the Assessment of Surgical sTaging vs Endoscopic ultrasound in lung cancer: a Randomised clinical (ASTER) trial to promote EBUS-TBNA and EBUS-FNA as the first staging procedure. 7 In the group staged by mediastinoscopy the false negative rate was unusually high and 18% of subsequent operations were for N2 disease.…”
Section: Preoperative Staging Must Be Comparable With Intraoperative mentioning
confidence: 99%